ANALISA KINERJA ORGANISASI PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA MAGELANG - Septyani, Eko Putri; Warsono, Hardi; Hariani, Dyah (Journal of Public Policy and Management Review, 2015)
Local government is given the authority to manage their own territory and meet the needs of society as more real. Meet the needs of the community will require optimal performance. Residence documents into one of the essential needs of the community and must be met, in addition to meeting the needs of education, health, economic and other needs. This research will analyze the performance conducted by the Department of Population and Civil Registration Magelang and aspects that support or hinder the performance of the agency. The theory used in this research is the theory of public administration and five performance criteria, namely the quantity, quality, timeliness, cost-effectiveness and accountability with descriptive qualitative research design. Data collection techniques used through interviews, observation and documentation of the employee informants Department of Population and Civil Registration Magelang and people processing documents. The results of this research indicate that, the performance of the Department of Population and Civil Registration Magelang in order to realize the possession of the document is still not optimal, especially in terms of quantity, also found problems such as disclosure of information, and the limited human resources, budget and infrastructure that support the performance. Nevertheless, the performance of the Department of Population and Civil Registration Magelang has been supported by the conformity of the program with the vision of service, proactive attitude to plan a more intensive effort to increase public awareness of the orderly ownership documents, the timeliness of the commitment for issuance of KTP/KK and birth certificate, discipline in creating accountability through performance reporting to the transparency of reporting. Overcome these problems, there are some suggestions that can be done such as expanding the information, especially the requirements of the documents with brochures and additional specialized personnel who are experts in delivering information, improving the quality of human resources, the addition of the proposed budget and improve the rehabilitation of infrastructure to be more adequate.